Reseña del libro Sistemas Fluviales: Organización, Evolución e Importancia Económica (Latin American Journal of Sedimentology and Basin Analysis, 2022)
This contribution is a brief review of the book “Sistemas Fluviales: Organización, Evolución e Importancia Económica”, which has been published by the Asociación Geológica Argentina thanks to the work of the Dr. José Matildo Paredes. The book includes ten chapters covering a wide variety of concepts of the fluvial systems, mainly sedimentologic and stratigraphic aspects, which were addressed at different temporo-spatial scales. The concepts developed are: i) Introduction; ii) Fluid Dynamics and Sediment Transport; iii) Texture, Sedimentary Structures and Facies; iv) Fluvial Architecture; v) Distal Floodplain; vi) Classifications of Fluvial Systems; vii) Allocyclic Controls; viii) Fluvial Reservoirs; ix) References; and x) Alphabetic Index. In this review, a critical brief description of each chapter was carried out with emphasis in those more relevant topics for understanding the dynamics of these particularly complex environments.